Inside Cover: Molecular Polygons Probe the Role of Intramolecular Strain in the Photophysics of π‐Conjugated Chromophores (Angew. Chem. Int. Ed. 5/2017). Issue 5 (4th January 2017) - Wilhelm, Philipp; Vogelsang, Jan; Poluektov, Georgiy; Schönfelder, Nina; Keller, Tristan J.; Jester, Stefan‐Sven; Höger, Sigurd; Lupton, John M.
Abstract : The π‐system of conjugated macromolecules can be bent in a controlled fashion by incorporating chromophores in molecular polygon templates. This distortion is clearly seen in scanning‐tunneling micrographs of the molecules. In their Communication on page 1234 ff. S. Höger, J. M. Lupton et al. show that bending leads to isotropic polarization in absorption and fluorescence but also affects the elementary photophysics. On the single‐molecule level, a correlation emerges between luminescence spectrum and lifetime, which arises from subtle variations in the bending radius between molecules.